Railway Stations on the BAM – from the XX to the XXI Century - Tkacheva, Marina; Avksentyuk, Vladimir (project baikal, 2019)
The Baikal-Amur Mainline is one of the most significant projects and realizations of the Soviet Union in the second half of the 20th century. The article considers the social and strategic importance of the BAM. It describes the railway stations on the Buryat section of the BAM, their construction peculiarities and their impact on architecture of the cities.